Calcium Channel Protein ORAI1 Mediates TGF-β Induced Epithelial-to-Mesenchymal Transition in Colorectal Cancer Cells - Kang, Qingjie; Peng, Xudong; Li, Xiangshu; Hu, Denghua; Wen, Guangxu; Wei, Zhengqiang; Yuan, Baohong (Frontiers in Oncology, 2021)
Accumulating evidence suggested that calcium release-activated calcium modulator 1(ORAI1), a key calcium channel pore-forming protein-mediated store-operated Ca2+ entry (SOCE), is associated with human cancer. However, its role in colorectal cancer (CRC) progression has not been well studied. Epithelial-mesenchymal transition (EMT) is a multistep process that occurs during the progression of cancers and is necessary for metastasis of epithelial cancer. Transforming growth factor-β (TGF-β) is a pleiotropic cytokine that has been shown to induce EMT. In this study, we are aimed at exploring the effects of ORAI1 on TGF-β1-induced EMT process in CRC cells. Herein, we confirmed ORAI1 expression was higher in CRC tissues than in adjacent non-cancerous tissues by using immunohistochemical staining and Western blot analysis. Higher ORAI1 expression was associated with more advanced clinical stage, higher incidence of metastasis and shorter overall survival. We compared ORAI1 expression in SW480 and SW620 cells, two CRC cell lines with the same genetic background, but different metastatic potential. We found ORAI1 expression was significantly higher in SW620 cells which exhibited higher EMT characteristics. Furthermore, knockdown of ORAI1 suppressed the EMT of SW620 Cells. After induced the EMT process in SW480 cells with TGF-β1, we found treatment of TGF-β1 showed a significant increase in cell migration along with the loss of E-cadherin and an increase in N-cadherin and Vimentin protein levels. Also, TGF-β1 treatment increased ORAI1 expression and was closely associated with the increase of SOCE. Silencing ORAI1 significantly suppressed Ca2+ entry, reversed the changes of EMT-relevant marks expression induced by TGF-β1, and inhibited TGF-β1-mediated calpain activation and cell migration. Finally, we blocked SOCE with 2-APB(2-Aminoethyl diphenylborinate), a pharmacological inhibitor. Interestingly, 2-APB and sh-ORAI1 both exhibited similar inhibition effects to the SW480 cells. In conclusion, our results demonstrated that ORAI1 could mediate TGF-β-Induced EMT by promoting Ca2+ entry and calpain activity in Colorectal Cancer Cells